2002
DOI: 10.1007/s001920200076
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Collagen in Parametrium and Vaginal Apex of Women with and without Uterine Prolapse

Abstract: Our objective was to compare the amount of collagen in parametrium and vaginal apex between women with uterine prolapse at pre- and postmenopause, and in women without prolapse. The study included 22 premenopausal women without prolapse (group A), 10 premenopausal women with prolapse (group B), and 23 postmenopausal women with prolapse (group C) (total 55). Patients in group A underwent abdominal hysterectomy for uterine leiomyoma, and patients in groups B and C underwent vaginal hysterectomy. During the surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 15 publications
1
22
1
5
Order By: Relevance
“…One study reported that collagen content was similar between prolapse patients and controls at the vaginal apex but was lower in the parametrial tissue [19]. The resiliency of the apical support structures such as the uterosacral ligaments has also been found to be significantly reduced among women with symptomatic uterovaginal prolapse [20].…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that collagen content was similar between prolapse patients and controls at the vaginal apex but was lower in the parametrial tissue [19]. The resiliency of the apical support structures such as the uterosacral ligaments has also been found to be significantly reduced among women with symptomatic uterovaginal prolapse [20].…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting with the above studies, Takano et al did not find any significant difference between the POP and control groups [14]. By using a Picrosirius polarization method, Borges et al observed a molecular disorganization and fragmentation of the collagen fibers in the lamina propria of women with POP [15].…”
Section: Collagenmentioning
confidence: 87%
“…Several studies have analyzed changes in the vaginal connective tissue of patients with and without POP by histology [12][13][14][15][16][17][18][19] using various methods and stainings to assess changes in collagen content in the vaginal wall. The results of these studies are described in Table 1.…”
Section: Collagenmentioning
confidence: 99%
“…Ocorre a formação de fibras menos elásticas que suportam menos tensão e estiramento [14][15][16][17][18] . Contudo, a real importância dos demais constituintes da matriz extracelular ainda está por ser esclarecida.…”
Section: Discussionunclassified